PENGARUH PEMBERIAN TRICHOKOMPOS SERASAH JAGUNG DAN NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glycine max L.) - Ardian, Ardian; Affandy, Aldy; Yoseva, Sri (Agros Journal of Agriculture Science, 2024)
Soybean productivity in Riau Province is low with high market demand. This researchl aims tol determine thel interaction effectl of givingl corn litter Trichocompost andl NPK fertilizer andl their respective effects onl the growthl and yield ofl soybean plants. Thel research wasl carried out atl the experimentall garden ofl the Facultyl of lAgriculture, Riaul University. Thel research wasl carried outl experimentally in factorial form which wasl prepared basedl on al completely randomizedl design (lCRD). Factor I is corn litter Trichocompost whichl consists ofl 3 doses andl factor II isl NPK fertilizerl which consistsl of 3 doses. Thel data obtainedl were analyzed statisticallyl using analysisl of variancel and continuedl with lDuncan's multiplel range testl at the 5% llevel. The parametersl observed werel plant lheight, numberl of primaryl branches, floweringl age, harvest lage, numberl of podsl per lplant, number of pithyl pods per plant, seedl weight perl plant, weightl of 100 seedsl and seed weightl per plot. Thel results ofl the research showedl that thel administration ofl 15 t.ha-1 Trichocompost corn litter with NPK 100 kg.ha-1 showed growth and production that tended to be better compared to other treatments in all parameters, except for flowering age and harvest age parameters. Keywords: Growth, Yield, Corn Litter Trichocompost, NPK INTISARIProduktivitas kedelai di Provinsi Riau termasuk rendah dengan permintaan pasar yang tinggi, Penelitianl ini bertujuanl untuk mengetahuil pengaruh interaksil pemberian Trichokompos serasah jagung danl pupuk NPK sertal pengaruhnya masing-masing terhadapl pertumbuhan danl hasil tanamanl kedelai. Penelitianl dilaksanakan dil kebun percobaanl Fakultas Pertanianl Universitas lRiau. Penelitianl dilakukan secaral eksperimental dalaml bentuk faktoriall yang disusunl berdasarkan rancanganl acak lengkapl (lRAL). Faktorl I yaitu Trichokomposl serasah jagung yang terdiril dari 3 dosis danl faktor II yaitu pupukl NPK yang terdiri dari 3 dosis. Data yang diperoleh dianalisisl secara statistikl menggunakan analisis ragaml dan dilanjutkanl dengan ujil jarak bergandal Duncan padal taraf l5%. Parameterl yang diamatil adalah tinggil tanaman, jumlah cabang primer, umurl berbunga, umur panen, jumlahl polong perl tanaman, jumlahl polong bernas perl tanaman, beratl biji perl tanaman, bobot 100l biji danl berat bijil per lplot. Hasill penelitian menunjukkan  bahwal  pemberian Trichokompos serasah jagungl 15 t.ha-1 dengan NPK 100 lkg.ha-1 memperlihatkan pertumbuhanl dan produksil yang cenderung lebihl baik dibandingkanl dengan perlakuanl lainnya pada semua parameter, kecuali parameter umurl berbunga danl umur lpanen. Kata Kunci: Pertumbuhan, lHasil, Trichokompos Serasah Jagung, NPK